The Effect of Company Profitability, Leverage, and Firm Size on Bond Ranking of Banking Companies Registered on The Indonesian Stock Exchange (IDX) for The Period 2015 - 2019 - Parulian; Nurul Suprihatin (Kusuma Negara Business School, 2020)
This study aims to determine the effect of profitability, leverage and firm size on bond ratings in banking companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2019 period. The sampling technique used was purposive sampling, in order to obtain a sample of 14 companies. This study uses logistic regression data analysis with the help of the eviews application. The results of this study indicate that profitability has no effect on bond ratings, leverage has no effect on bond ratings, firm size has no effect on bond ratings.